Stigmatization of Household Mother with HIV/AIDS in Tulungagung District, East Java, Indonesia - RIO ADY ERWANSYAH; Nursalam Nursalam; Ferry Efendy (International Journal of Nursing and Health Services (IJNHS), 2020)
Stigma is an assessment of behavior or character that is not fair or gives a negative title to a particular person or group that aims to isolate. The study aimed to explore the experience of housewives with HIV AIDS about the stigma experienced by health workers. A qualitative method with a phenomenological approach was applied in this study. Eleven informants were selected from Tulungagung Regency area. We conducted the data collection using the in-depth interview; data analysis was carried out according to Collaizi's steps. The results of this study are information about the stigmatized experience of PLWHA, namely 1) Writing identity with a specific code, 2) HIV status of informants was discussed by nurses at the hospital, Using gloves and masks when handling, even if only limited to checking body temperature, 3) Separation of hospitalization rooms while undergoing hospitalization, 4) Not given health services because of the unavailability of drugs when sick, This research shows that there is still a stigma received by PLHIV from health workers, so that further treatment of stigma in health care institutions is needed to improve the professionalism of health services, health workers in health care agencies must be able to provide fair services to every patient who needs health care and maintain patient privacy